BUILDING THE GAME WORLD: ENVIRONMENT AND DETAILS IN 3D GAMES - Kurbanov Khurshid (Galaxy International Interdisciplinary Research Journal, 2024)
Creating environments in 3D games completely changes the experience of players. The environment allows the players to feel the game world and get deeper into it. This article details the techniques and processes involved in creating environments and details in 3D games.